Dyrektor szkoły jako menedżer oświaty - Leżucha, Magdalena (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The study focuses on the role of the principal as an education manager, important and desirable for the functioning and effectiveness of the school’s impact. The starting point for consideration is an approximation of the roles of the headteacher today, the managerial functions and tasks he fulfills: planning, organizing, motivating and controlling. The concept of educational leadership, the role and desirable skills of education manager are presented. Currently, the director consolidates many functions and roles, he is not only a teacher, manager, supervisor, leader but also a visionary who is able to convince others, not only employees, but also cooperating entities to his ideas and visions. Takes care of the school’s development, builds its potential and adjusts the offer to market conditions and prevailing competition